Groundwater Variability In Bangladesh: Assessment Based On Rainfall Variation And Use Of Water In Irrigation - Sumiya, Nazmoon Nahar; Khatun, Hafiza (Journal of the Asiatic Society of Bangladesh, Science, 2016)
This study attempts to portray the scenario of groundwater level with respect to rainfall variability and its use for irrigation purpose for rice production in Bangladesh. Data on groundwater level and irrigation water usage were collected from BWDB and BBS. The changing pattern of groundwater level are presented in maps using Inverse Distance Weighted (IDW) interpolation method in ArcGIS 10.3. Analysis shows the increasing dependency on groundwater than on surface water for irrigation purpose at varied range across the country. The groundwater level is declining at a higher rate in northern parts of the country than the southern parts. In the context of climatic variability, excessive use of groundwater can trigger the lowering of groundwater level which will require more energy to uptake water for irrigation and so the input cost of production of rice will be increased. Therefore, apposite measures are required to ensure sustainable use of groundwater resources. Asiat. Soc. Bangladesh, Sci. 42(2): 177-189, December 2016